Effect of surfactant assisted sonic pretreatment on liquefaction of fruits and vegetable residue: Characterization, acidogenesis, biomethane yield and energy ratio. (September 2018) - Shanthi, M.; Rajesh Banu, J.; Sivashanmugam, P.
Graphical abstract: Highlights: Surfactant aided sonic pretreatment method was studied on fruits and vegetable waste. At 5400 kJ/kg TS, combined pretreatment achieved 26% dissolve organic release. Maximum of 72% delignification was achieved in combined pretreatment. Combinative pretreatment accomplished improved VFA and methane yield. Energy ratio for surfactant aided sonic pretreatment is greater than sonication. Abstract: The present study explored the disintegration potential of fruits and vegetable residue through sodium dodecyl sulphate (SDS) assisted sonic pretreatment (SSP). In SSP method, initially the biomass barrier (lignin) was removed using SDS at different dosage, subsequently it was sonically disintegrated. The effect of SSP were assessed based on dissolved organic release (DOR) of fruits and vegetable waste and specific energy input. SSP method achieved higher DOR rate and suspended solids reduction (26% and 16%) at optimum SDS dosage of 0.035 g/g SS with least specific energy input of 5400 kJ/kg TS compared to ultrasonic pretreatment (UP) (16% and 10%). The impact of fermentation and biomethane potential assay revealed highest production of volatile fatty acid and methane yield in SSP (1950 mg/L, 0.6 g/g COD) than UP. The energy ratio obtained was 0.9 for SSP, indicating proposed method is energetically efficient.